2023
DOI: 10.1101/2023.05.20.541586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noradrenergiclocus coeruleusactivity functionally partitions NREM sleep to gatekeep the NREM-REM sleep cycle

Abstract: The noradrenergic locus coeruleus (LC) supports vital brain functions during wakefulness. In contrast, the LC has been associated with sleep-promotion and -disruption, leaving its functions for sleep uncertain. Here, we show that the LC is essential for the progression of natural, undisturbed sleep because it creates a non-reducible timeframe for the non-rapid-eye-movement (NREM) sleep-REM sleep cycle. Fiber-photometric jGCaMP8s-based LC activity measures, closed-loop optogenetics and mouse sleep-wake monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 103 publications
(277 reference statements)
0
6
0
Order By: Relevance
“…As soon as a REMs episode was detected, a small vibrating motor attached to the animal’s head was turned on to terminate REMs by briefly awakening the animal ( Fig. 3A, S5A ) (Cardis et al, 2021; Osorio-Forero et al, 2023). Compared with the baseline recordings from the same mice during the same circadian time, we found that 6 h of REMs restriction (ZT 1.5-7.5) significantly reduced the amount of REMs and duration of REMs episodes, while increasing their frequency ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As soon as a REMs episode was detected, a small vibrating motor attached to the animal’s head was turned on to terminate REMs by briefly awakening the animal ( Fig. 3A, S5A ) (Cardis et al, 2021; Osorio-Forero et al, 2023). Compared with the baseline recordings from the same mice during the same circadian time, we found that 6 h of REMs restriction (ZT 1.5-7.5) significantly reduced the amount of REMs and duration of REMs episodes, while increasing their frequency ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We employed an automatic REMs detection algorithm (Weber et al, 2015, 2018; Stucynski et al, 2022; Schott et al, 2023) and used a small vibrating motor to terminate/restrict REMs (Cardis et al, 2021; Osorio-Forero et al, 2023) (https://github.com/luthilab/IntanLuthiLab). A small vibrating motor (DC 3V Mini Vibration Motor, diameter: 10mm, thickness: 3mm, BOJACK) with a soldered lobster claw clasp was attached to a small wire hook secured in the dental cement of each mouse head.…”
Section: Methodsmentioning
confidence: 99%
“…Such algorithms could also be adapted for use in the clinical setting. Animal studies have recently provided interesting EEG readouts of arousal system activity (for instance of the locus coeruleus), which appear to hold true for humans (Kjaerby et al, 2022;Lecci et al, 2017;Osorio-Forero et al, 2023). Translational studies of this type will be crucial to better understand which networks and neuro-modulatory systems are involved in sleep perception and to plan studies evaluating the effect of specific pharmacological manipulations on subjective sleep quality.…”
Section: Within-subject Contrast and Correlations (Serial Awakening P...mentioning
confidence: 99%
“…As soon as a REMs episode was detected, a small vibrating motor attached to the animal's head was turned on to terminate REMs by briefly awakening the animal (Fig. 3A , S4A ) (Cardis et al, 2021 ;Osorio-Forero et al, 2023 ). Compared with the baseline recordings from the same mice during the same circadian time, we found that 6 h of REMs restriction (ZT 1.5-7.5) significantly reduced the amount of REMs and duration of REMs episodes, while increasing their frequency (Fig.…”
Section: Poa Gad2 →Tmn Neurons Exhibit An Increased Number Of Calcium...mentioning
confidence: 99%
“…We employed an automatic REMs detection algorithm (Weber et al, 2015(Weber et al, , 2018Stucynski et al, 2022 ;Schott et al, 2023 ) and used a small vibrating motor to terminate/restrict REMs (Cardis et al, 2021 ;Osorio-Forero et al, 2023 ) (https://github.com/luthilab/IntanLuthiLab ). A small vibrating motor (DC 3V Mini Vibration Motor, diameter: 10mm, thickness: 3mm, BOJACK) with a soldered lobster claw clasp was attached to a small wire hook secured in the dental cement of each mouse head.…”
Section: Rems Restrictionmentioning
confidence: 99%